Development of Doratoon Video Learning Media Based on Local Wisdom for Students' Understanding of Fraction Concepts in Grade IV - Khodijah, Nurhasanah Dwi; Juwita, Putri; Sukmawarti, Sukmawarti (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2025)
This study aims to develop local wisdom-based video doratoon learning media for understanding the concept of fractions of grade IV students and determine the validity, practicality, and effectiveness of the learning media developed. The type of method used in this research is development (Research and Development) using the 4D development procedure model which consists of 4 stages namely Define (definition), Design (plaħning). Development (development), Dissemination (dissemination). This research uses instruments, namely validation sheets in the form of questionnaires or questionnaires given to validators of material experts, media experts, teacher responses, student responses, and tests of understanding of local wisdom-based fraction concepts given to students. The subjects in this study were media expert validators, material experts, teachers, and grade IV students totaling 20 people. Based on the trials conducted, the results of the validity of the learning media development were 97.22% with very valid criteria, and the validity of the learning material was 95% with very valid criteria. The results of the practicality level were 83% student response, and 92% teacher response with very practical criteria. For the level of effectiveness obtained by 89% very effective criteria, and on the n gain score of 74% with high criteria. So it can be concluded that the doratoon video learning media based on local wisdom for understanding the concept of fractions of fourth grade students.